Methane purification from landfill using PVC based membrane - Sunarti, Abd Rahman; Roshan, Raj Krishna; Norhidayana, Mandayar; Nadia Sofea, Hazleen; Sureena, Abdullah (Nova Science Publishers, 2019)
The closing study analyzes the permeability and selectivity of carbon dioxide and methane gas of polyvinylchloride mixed matrix membrane with the inorganic fillers of zeolite 4Å particles. The fabrication of mixed matrix membranes is prepared by using dry/wet phase inversion method, and Fourier transform infrared spectroscopy is used to study the chemical interaction of the membrane by analyzing the intensity of the peak of chloride vibration.